Effects of Parental Attitudes Toward Spousal Violence on Early Childhood Development and Learning Support Among Ghanaian Children. Issue 3 (February 2022) - Kofinti, Raymond Elikplim; Ewusie, Ewura - Adwoa; Kwaah, Christopher Yaw; Asmah, Emmanuel Ekow
The prevalence of condoning attitudes toward spousal violence (SV) is high in Ghana, yet much is not known about how the development of children is compromised in households where attitudes toward SV are tolerated. This study is premised on two objectives: (a) examination of the effect of parents condoning attitudes toward SV on early childhood development; and (b) investigation of the effect of parents condoning attitudes toward SV on the amount of learning support children receive from household members. Data on 2, 740 children aged between 36 and 59 months were drawn from the 2011 Ghana Multiple Indicator Cluster Survey for the first objective and 1, 595 households with children aged between 4 and 15 years were sourced from the 2014 Ghana Demographic and Health Survey for the second. Analytical methods employed are descriptive statistics, instrumental variable (IV), and ordinary least squares (OLS) micro-econometric estimation techniques. The findings suggest that parents who condone attitudes toward SV reduce early childhood development by 3.269 units. Compared with the physical and socioemotional domains, parents tolerating attitudes toward SV have the highest adverse effect on the literacy, numeracy, and learning development domain of early childhood development (2.916 units). In addition, households that accept attitudes toward SV reduce the amount of learning support offered to children by 0.261 units, and every additional attitude toward SV acceptance reduces child learning support by 0.079 units. Attitudes of parents toward condoning SV retard the early development of children, impair children's cognitive development, and compromise the amount of learning support children receive from household members. This study reinforces the evidence that parental attitudes are related to child outcomes in Ghana. The evidence calls for strengthening healthy family environments and child protection systems through behavioral change communication interventions and awareness creation among parents.